Prophylactic risk-reducing salpingo-oophorectomy in BRCA mutation carriers: what is going on in a region of northern Italy?. (January 2021) - Grandi, Giovanni; Perrone, Anna Myriam; Perrone, Antonino; Mandato, Vincenzo Dario; Comerci, Giuseppe; Sammarini, Margaret; Merisio, Carla; Amadori, Andrea; Stefanetti, Marco; Martinello, Ruby; Facchinetti, Fabio; De Iaco, Pierandrea; et al.
Highlights: Breast cancer survivors underwent risk-reducing salpingo-oophorectomy at a younger age. The temporal trend for the age distribution of risk-reducing salpingo-oophorectomy was similar for BRCA1 and BRCA2 mutation carriers. All diagnoses of ovarian invasive cancer were made for BRCA1 or BRCA-combined subjects. Abnormal tubal findings were mainly found by pathologists in university hospitals. In none of the few women who underwent concomitant or subsequent hysterectomies was a primitive uterine endometrioid or serous cancer found. Abstract: Background: BRCA1 mutation carriers are recommended to undergo prophylactic risk-reducing salpingo-oophorectomy (RRSO) between the ages of 35 and 40 or when child bearing is complete, with a possible delay until age 40–45 for BRCA2 mutation carriers. Study Question: Primary outcome was the rate of unsuspected cancer findings during RRSO in a region of northern Italy (Emilia Romagna) and secondary outcomes were details of RRSO: age at surgical intervention, the venue of the procedures in relation to the surgical/pathological quality and the rate/role of concomitant opportunistic hysterectomies. Study Design: Multicentre data collection by invitation to report current RRSO practices. Results: A total of 222 RRSOs (54.5 % BRCA1, 34.7 % BRCA2, 1.8 % BRCA1 and BRCA2 combined, 5.8 % BRCA-VUS and 3.2 % BRCA not better specified) were reported from 9 different centres, half in non-university hospitals and the remainder in university hospitals. Breast cancer survivors (56.3 %) underwent the RRSO at a younger age (47.8 vs 50.6 years, p  =  0.02). The mean and median ages at surgical intervention (49.0 and 48.0, respectively) were similar for BRCA1 and BRCA2 mutation carriers, as was the temporal trend in age distribution, and proportions treated in university and non-university hospitals. A diagnosis of ovarian invasive cancer was reported in 3.5 % of subjects, all BRCA1 or BRCA-combined subjects, at a median and mean age of 57 years (range 42–68). Abnormal tubal findings, such as serous tubal intraepithelial lesions (STIL) (100 %), secretory cell outgrowth (SCOUT) (100 %) and STIC (71.4 %), were mainly reported by pathologists in university hospitals. Of the 222 procedures, 15 (6.7 %) included hysterectomies: in none of these cases was a primitive uterine endometrioid or serous cancer found. Conclusions: The results from this multicentre regional study should guide future preventive health policies for RRSO in BRCA mutation carriers.